Analysis of Copyright Protection of AI Works from the Perspective of the MUI Fatwa - Saputra, Chandra Akbar; Zahara, Fatimah (Universitas Islam Negeri Alauddin Makassar, 2026)
The rapid development of Artificial Intelligence (AI) raises complex legal questions regarding ownership and copyright protection of works generated through algorithmic systems. AI can produce text, images, music, and other creative outputs with economic value, yet it lacks legal personality, intention, and moral responsibility. This situation creates normative challenges in both contemporary copyright law and Islamic legal discourse, particularly in determining ownership and accountability for AI-generated works. In Islamic law, the absence of explicit classical rulings on AI-based creativity requires new interpretative approaches that integrate traditional legal principles with modern technological realities. This study aims to analyze the construction of ownership and copyright protection of AI-generated works from the perspective of Islamic law by examining the normative principles contained in the fatwas of the Indonesian Ulema Council (MUI). The research employs normative legal methods using conceptual, statutory, and maqasid al-shari‘ah approaches based on library research. The findings show that AI-generated works can be classified as mal hukmi (intangible property) because they possess economic value, utility, and social recognition. Their protection therefore aligns with the principle of hifz al-mal. Although no MUI fatwa explicitly regulates AI copyright, the principles in MUI Fatwa No. 24 of 2017 indicate that digital systems function only as instruments (wasilah), while legal responsibility remains with humans. Consequently, AI cannot be considered a legal subject, and copyright ownership is most appropriately attributed to users who actively direct the creative process. This study demonstrates that Islamic law, through maqasid al-shari‘ah and contemporary fatwas, provides a normative framework for addressing emerging issues of AI governance and intellectual property in the digital era.